Foreign Publications about Improving the International Legal Mechanisms for the Ecosystem-based Management in the Arctic - Inna P. Dudykina (Московский журнал международного права, 2016)
The article shows, in the context of international legal studies, legal instruments of the ecosystem-based management approach and the environmental management in the Arctic, the content of such instruments and peculiarities of its use in the High North.